A survey of linyphiid spiders from Xishuangbanna, Yunnan Province, China (Araneae, Linyphiidae) - Qingyuan Zhao; Shuqiang Li (ZooKeys, 2014)
Eight new genera and 30 new species are described: Cirrosus gen. n. (type species Cirrosus atrocaudatus sp. n. (♂♀)), Conglin gen. n. (type species Conglin personatus sp. n. (♀)), Curtimeticus gen. n. (type species Curtimeticus nebulosus sp. n. (♂)), Gladiata gen. n. (type species Gladiata fengli sp. n. (♂)), Glebala gen. n. (type species Glebala aspera sp. n. (♂)), Glomerosus gen. n. (type species Glomerosus lateralis sp. n. (♂)), Smerasia gen. n. (type species Smerasia obscurus sp. n. (♂♀)), Vittatus gen. n. (type species Vittatus fencha sp. n. (♂♀)); Batueta cuspidata sp. n. (♂♀), Capsulia laciniosa sp. n. (♂), Dactylopisthes separatus sp. n. (♀), Gongylidiellum bracteatum sp. n. (♀), Houshenzinus xiaolongha sp. n. (♂♀), Laogone bai sp. n. (♂), L. lunata sp. n. (♂♀), Maro bulbosus sp. n. (♀), Nasoonaria circinata sp. n. (♂♀), Neriene circifolia sp. n. (♂♀), Oedothorax biantu sp. n. (♀), Oilinyphia hengji sp. n. (♂♀), Paikiniana furcata sp. n. (♂♀), Parameioneta bishou sp. n. (♂♀), P. multifida sp. n. (♂♀), P. tricolorata sp. n. (♂♀), Tapinopa undata sp. n. (♂), Theoa bidentata sp. n. (♂♀), Theoa vesica sp. n. (♂♀), Vittatus bian sp. n. (♂♀), V. latus sp. n. (♂♀), V. pan sp. n. (♂♀). The male of Kaestneria bicultrata Chen & Yin, 2000 and the females of Asiagone perforata Tanasevitch, 2014 and Batueta similis Wunderlich & Song, 1995 are described for the first time; photos of Bathyphantes paracymbialis Tanasevitch, 2014 are provided.